PROCESS TYPES ON STUDENTS’ PERSUASIVE TEXT: A SYSTEMIC FUNCTIONAL LINGUISTICS STUDY - Sari, Puspita; Gunawan, Hero; CM Simatupang, Ervina (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
This research is entitled Process Types on Students' Persuasive Text: A Systemic Functional Linguistics Study. The purpose of this research is to find out (1) what types of transitivity processes are found in student persuasion texts; and (2) what processes appear most dominant in the text. The theory used in this research is the Systemic Functional Linguistics (SFL) theory which refers to the thinking of Halliday (2014). The research method used is a qualitative descriptive method. The data obtained was based on the results of students' persuasive writing with the title